Analysis of Challenges faced by Huawei on the launching of 5G Technology and the Strategies to Overcome it. - Lin, Ch’ng Jia; Kee, Daisy Mui Hung; Chee, Chaw Ke; Ng, Cynthia; Yao, Tang (AIBPM Publisher, 2019)
Huawei technologies co., ltd. is a leading global provider of information and communications technology (ICT) infrastructure and smart devices based out of China.1 With integrated solutions across four key domains which are telecommunication networks, IT, smart devices, and cloud services, Huawei are committed to bringing digital to every person, home and organization for a fully connected, intelligent world. Huawei's end-to-end portfolio of products, solutions and services are both competitive and secure. Through open collaboration with ecosystem partners, the company create lasting value for customers, working to empower people, enrich home life, and inspire innovation in organizations of all shapes and sizes. At Huawei, innovation focuses on customer needs. Huawei invest heavily in basic research, concentrating on technological breakthroughs that drive the world forward. Huawei's success in penetrating the global market has been attributed to various potent factors and organisation culture is one that form the basic behind success. Hence, it is interesting to explore the specific values that define the culture of Huawei which distinct its well-attained accomplishment from other competitors. However, it is critical to note that the overwhelming success experienced by the Huawei today was actually guided and influenced heavily by the thinking and vision of its founder, Ren Zhengfei. He is known as a leader who inspires and motivates people to pursue innovation at all levels and at the same time adopts a reflective and self-criticising attitude, especially in times of success. Huawei may face challenges which included strong competitors in market like Samsung, Apple and others, the need for improvement to be made from the previous mobile communication technology, the challenges of 5G technology to be implement, the country like US banned Huawei to penetrate in their market as security threat and many. Although Huawei’s 5G may contribute to an enormous amount of benefits in a variety of sectors but, despite its substantial benefits, it has drawn lots of challenges amid its launching. By launching 5G, it is the most effectively way to compete with other company which had the strong brand advocacy of their products. Fifth generation wireless (5G) is a wireless networking architecture built on the 802.11ac IEEE wireless networking standard, which aims to increase data communication speeds by up to three Huawei times compared to its predecessor, 4G (IEEE 802.11n).